Kajian Semiotika Iklan Produk Kosé Cosmeport (Jurnal Pustaka, 2025)
Advertising is one of the media that is used to deliver messages. A company can communicate a message about the product on sale so that it will be known to the audience with advertising. KOSÉ Cosmeport is a cosmetic company that markets its products using advertising posters. This research aims to describe the advertising messages contained in five advertising posters for KOSÉ Cosmeport facial cosmetics. This research was studied using semiotics theory by Barthes (1988) and semiotics in advertising theory by Barthes (2010). The methods used in this research are literature study methods and qualitative methods. The results of this research show that the five advertising posters contain three types of messages, namely (1) Linguistic messages in the form of text displayed on the advertising posters. (2) Coded iconic message that refer to icons as advertising signifiers. (3) Non-coded iconic message is a combination of the linguistic message and the coded iconic message in the advertising poster.